Postpartum Hemorrhage Requiring Transfusion and Risk of Cardiovascular Disease Later in Life: A Retrospective Cohort Study. Issue 4 (22nd December 2021) - Cho, G.J.; Lee, K.M.; Kim, H.Y.; Han, S.W.; Oh, M.J.; Chiec, L.; Chae, Y.K.
Abstract : ( BJOG . 2021;128:738–744. doi: 10.1111/1471-0528.16515) Roughly 20% of worldwide maternal deaths are due to postpartum hemorrhage (PPH). Currently occurring in 6% to 11% of births worldwide, the incidence of PPH is on the rise. PPH severely impacts maternal mortality and morbidity rates, leading to outcomes such as increased intensive care unit (ICU) admission, increased risk of stroke, and increased risk for heart disease. Most current research identifies risks immediately following childbirth or during the puerperium while long-term risks are relatively unstudied. This study aimed to identify whether PPH is associated with long-term cardiovascular disease (CVD) such as cerebrovascular disease (CV) and ischemic heart disease (IHD).